EMPTY CATEGORIES IN TRANSFORMATIONAL RULES - Adha, Ruly (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2019)
There are three theories that are always developed in any study of language, namely theory of language structure, theory of language acquisition, and theory of language use. Among those three theories, theory of language structure is regarded as the most important one. It is assumed that if someone knows the structure of language, he/she can develop theories about how language is acquired and used. It makes Chomsky interested in developing the theory of language structure. Chomsky introduced a theory of grammar called Transformational Generative Grammar or Transformational Syntax. Transformational Syntax is a method of sentence fomation which applies some syntactic rules (or also called transformational rules). Transformational rules consist of three types, namely movement transformation, deletion transformation, and substitution transformation. When those transformational rules are applied in a sentence, they will leave empty categories. Empty categories can be in the form of Complementizer (Comp), Trace, and PRO. This article will elaborate those empty categories; their appearance in the transformational rules; and the characteristics of each empty category.